Influência de parâmetros morfométricos e do uso e ocupação da terra na densidade de cianobactérias em bacias hidrográficas de captação de água para abastecimento público - Souza, Cláudia Alves de (2017)
The quality of water and the development of cyanobacteria in water courses results from the use and occupation of land and the physical parameters of the river basin. Therefore, the objective of this work was to study the water quality and the influence of physical-chemical, morphometric, land use and occupation and soil loss on the development of cyanobacteria in 15 water catchment basins for public water supply, in the period from 2007 to 2016. To evaluate the correlation between the parameters, the non-parametric regression model Kernel Regression with Mixed Data Types was used, at a significance level of 10% with p-value <0.1. The IQAACP and IQACWQI were applied to evaluate the water quality of the abstraction sources. For IQACWQI, 86% of the basins were classified in the categories between excellent and regular; and only the stream Lajes and the stream Veredas were classified in at least one period in the categories poor or very poor. For IQAACP, the IQA1 of the hydrographic basins analyzed for the first main component was explained by between 29% and 54%. The reduction of the average density of cyanobacteria promoted lower values of IQA1, and therefore, better water quality. The IQAp values were lower in relation to the IQA1, improving water quality. The most significant parameters in the definition of water quality for the first main component were: dissolved oxygen, biochemical oxygen demand, ammoniacal nitrogen and turbidity. The correlation of cyanobacteria density was positive with pasture and urban area and negative with APP vegetation. Positive correlations were found between cyanobacteria density and physico-chemical parameters (chlorophyll a, pheophytin, water temperature, ammoniacal nitrogen, nitrate and dissolved inorganic nitrogen). Among dissolved solids and cyanobacteria density, negative correlation was found for the Meia Ponte basin and positive for the Samambaia stream basin. Given this scenario, it is necessary to restore the natural vegetation areas in APP and reduce the anthropic areas, ensuring availability and quality of water for public supply.